Flumazenil Pretreatment Reduces Mefenamic Acid-Induced Central Nervous System Toxicity in Mice - Jarrar, Qais; Ayoub, Rami; Jarrar, Yazun; Aburass, Hadeel; Goh, Khang Wen; Ardianto, Chrismawan; Long, Chiau Ming *; Moshawih, Said; Alfaqih, Hussain (IMR Press, 2023)
Background: Mefenamic acid (MFA), a common analgesic, causes central nervous system (CNS) toxicity at high doses with a proposed activity on the Gamma-aminobutyric acid (GABA) system. However, it remains unknown whether flumazenil (FMZ), a GABA type A receptor (GABAAR) antagonist, can reverse MFA toxicity.